Pengaruh Psikoedukasi Efikasi Diri terhadap Kesulitan Pemilihan Jurusan pada Siswa SMA “X” Bandung - Dwi Cahya Oktarina; Maria Yuni Megarini Cahyono; Jane Savitri (Universitas Medan Area, 2026)
This experimental study aims to test the effect of Career Decision-Making Self-Efficacy (CDMSE) psychoeducational intervention on reducing Career Decision-Making Difficulties (CDMD) in high school students. Participants consisted of 40 eleventh-grade students who were randomly divided into experimental (n = 20) and control (n = 20) groups. The experimental group participated in three intensive psychoeducational sessions in one day designed based on the five core competencies of CDMSE, while the control group did not receive any intervention. CDMD was measured using the Gati adaptation scale at the pretest and posttest stages. The results of data analysis using the Wilcoxon Signed Rank Test and the Mann–Whitney U Test showed no significant difference in CDMD scores after the intervention, either in the experimental group or compared to the control group. These findings indicate that intensive intervention in one day is not enough to provide space for reflective thought and internalization of competencies to form self-efficacy, so that future programs need to distribute sessions periodically, include independent tasks that are evaluated as a source of performance accomplishments, and adjust the terminology of